Preventing Gender-Based Violence: Portuguese Youth Perspectives on Primary Prevention Programs - Camila Iglesias; Raquel Rodrigues; Ana Guerreiro; Cátia Pontedeira; Maria José Magalhães (Social Sciences)
Gender-based violence (GBV) remains a pressing societal issue that requires urgent attention. Although there have been efforts to implement GBV prevention programs in Portugal, research assessing their long-term impact on young people is notably scarce. This study seeks to address this gap by examining the perceptions and experiences of young individuals involved in these programs. The research captures a comprehensive view of the participants’ perspectives through in-depth interviews. The findings reveal personal and interpersonal effects from participation in GBV prevention initiatives. They highlight the necessity for such programs to commence in early childhood to maximize their effectiveness and societal impact over time. Moreover, the research indicates that these initiatives influence youth’s personal development, relationships, career aspirations and professional choices. Consequently, this study advocates for the broader implementation of holistic GBV prevention programs in educational settings and calls for further investigation into their long-lasting outcomes. It emphasizes the importance of adopting a holistic, structured, and interactive approach to primary prevention, ultimately empowering future generations and creating a safer society for all.